2006
DOI: 10.1063/1.2390710
|View full text |Cite
|
Sign up to set email alerts
|

Entropy, diffusivity, and structural order in liquids with waterlike anomalies

Abstract: The excess entropy, S e , defined as the difference between the entropies of the liquid and the ideal gas under identical density and temperature conditions, is shown to be the critical quantity connecting the structural, diffusional and density anomalies in water-like liquids. Based on simulations of silica and the two-scale ramp liquids, water-like density and diffusional anomalies can be seen as consequences of a characteristic non-monotonic density dependence of S e . The relationship between excess entrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
204
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 185 publications
(210 citation statements)
references
References 57 publications
5
204
0
1
Order By: Relevance
“…These multiple structural and dynamical anomalies, and their interrelation, has been seen before in bounded potentials, 29,30 in liquids with water-like anomalies 31 and colloids with short-ranged attractions. 32 This suggests that crystallization and fluid dynamics are inextricably connected, and that this connection is not independent of the underlying crystal structure.…”
Section: Discussionmentioning
confidence: 99%
“…These multiple structural and dynamical anomalies, and their interrelation, has been seen before in bounded potentials, 29,30 in liquids with water-like anomalies 31 and colloids with short-ranged attractions. 32 This suggests that crystallization and fluid dynamics are inextricably connected, and that this connection is not independent of the underlying crystal structure.…”
Section: Discussionmentioning
confidence: 99%
“…Thermodynamic anomalies do not occur only in water, experiments for T e 40 , Ga, Bi, S 41,42 and Ge 15 T e 85 43 , liquid metals 44 and graphite 45 and simulations for silica [46][47][48] , silicon 49 and BeF 2 46 shown that these system also have thermodynamic anomalies. In addition, silica 48,50 and silicon 51 show diffusion anomalous behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, silicon 33 and others material, as silica [34][35][36] shows thermodynamic anomalies 31 , while silicon 44 and silica 33,35,36,45 show a maximum in the diffusion coefficient at constant temperature. These systems and their density and diffusion anomalies can be described in an effective way by a two length scale core-softened potential.…”
Section: Introductionmentioning
confidence: 99%